Fotovoz. Miradas y voces de los sujetos sociales. - Castro Sánchez, Ana Elisa; Avila Ortiz, María Natividad; Farías Campero, María del Carmen (Editorial Universitaria ; AM Editores ; CLAVE Editorial, 2025)
DOI: http://doi.org/10.29105/b-30587